2018
DOI: 10.1007/jhep11(2018)028
|View full text |Cite
|
Sign up to set email alerts
|

Running of fermion observables in non-supersymmetric SO(10) models

Abstract: We investigate the complete renormalization group running of fermion observables in two different realistic non-supersymmetric models based on the gauge group SO(10) with intermediate symmetry breaking for both normal and inverted neutrino mass orderings. Contrary to results of previous works, we find that the model with the more minimal Yukawa sector of the Lagrangian fails to reproduce the measured values of observables at the electroweak scale, whereas the model with the more extended Yukawa sector can do s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Throughout this paper, we will focus on the non-supersymmetric case whenever we discuss specific examples. For discussions of the phenomenological viability of minimal non-supersymmetric SO(10) models see, e.g., [106][107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122]. If an extension of the Reuter fixed point to the supersymmetric GUT setting should exist, see [123], our discussion would carry over to that case.…”
Section: Jhep08(2020)111mentioning
confidence: 99%
“…Throughout this paper, we will focus on the non-supersymmetric case whenever we discuss specific examples. For discussions of the phenomenological viability of minimal non-supersymmetric SO(10) models see, e.g., [106][107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122]. If an extension of the Reuter fixed point to the supersymmetric GUT setting should exist, see [123], our discussion would carry over to that case.…”
Section: Jhep08(2020)111mentioning
confidence: 99%
“…As neutrino data became available to the level of precision that allowed fits to be made, the initial attempts to accommodate neutrino masses and leptonic mixing parameters were performed for SUSY models [11][12][13][14][15][16] with the type-I or type-II seesaw mechanism, or a mixture thereof. There have also been numerous fits of the Yukawa sector of various non-SUSY models with type-I seesaw [17][18][19][20][21][22][23], with the conclusion that these fits are possible depending on the specifics of the Yukawa sector and the symmetry breaking pattern. Furthermore, fits with type-II seesaw or a combination of types I and II seesaw have been considered in non-SUSY scenarios [24,25], which concluded that models with type-II seesaw only do not yield acceptable fits, but that type-II seesaw in combination with type-I seesaw provides good fits.…”
Section: Introductionmentioning
confidence: 99%
“…Models based on a Pati-Salam intermediate symmetry have been investigated extensively in the literature [10,35,47,[67][68][69][70][71][72]. In this work, we follow the model described in Ref.…”
Section: No Intermediate Symmetrymentioning
confidence: 99%